ChemInform Abstract: Cation Effect on Formation of Preyssler‐Type 30‐Tungsto‐5‐phosphate: Enhanced Yield of Na‐Encapsulated Derivative and Direct Synthesis of Ca‐ and Bi‐Encapsulated Derivatives. Issue 6 (21st January 2016) - Hayashi, Akio; Haioka, Terufumi; Takahashi, Keita; Bassil, Bassem S.; Kortz, Ulrich; Sano, Tsuneji; Sadakane, Masahiro
Abstract: The effect of metal cations in reaction mixtures for the preparation of the title anion is investigated leading to large scale (27g) synthesis of (IV) with improved yield, and the encapsulation of Ca 2+ and Bi 3+ .